2012
DOI: 10.5812/archcid.15087
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatis Detection by Nested-PCR Method on Females Referred to Medical Centers of Tehran, Iran

Abstract: Background:Chlamydia trachomatis (C. trachomatis) is the most common sexually transmitted bacterial infectious disease in the world. Moreover, it plays a role in spontaneous abortion. The accuracy of PCR in detection of C. trachomatis infections has been shown in several studies. Objectives: The frequency of spontaneous abortion and known side effects and statistics vary in Chlamydia trachomatis infection in women with spontaneous abortion and different ways to identify and determine the prevalence of Chlamydi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
(15 reference statements)
0
7
1
Order By: Relevance
“…U. urealyticum is among the most common organisms causing adverse infections of the amniotic fluid and placenta (9). It is known as a normal flora in the lower genital tract, but its association with STDs is still controversial (9). To the best of our knowledge, this is the first report about the frequencies of C. trachomatis, U. urealyticum, and M. genitalium infections in pregnant or women with abortion in southeast of Iran.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…U. urealyticum is among the most common organisms causing adverse infections of the amniotic fluid and placenta (9). It is known as a normal flora in the lower genital tract, but its association with STDs is still controversial (9). To the best of our knowledge, this is the first report about the frequencies of C. trachomatis, U. urealyticum, and M. genitalium infections in pregnant or women with abortion in southeast of Iran.…”
Section: Introductionmentioning
confidence: 88%
“…DNA extraction and amplification for all polymerase chain reaction (PCR) and nested PCR assays were performed using Pars Tous kit (Arya Tous CO. Iran), which amplifies outer membrane protein 1 (omp 1) of C. trachomatis, P protein (mgpa) of M. genitalium, and urease of U. urealyticum (9,15,16). For C. trachomatis, nested PCR was performed according to the kit's instructions ( Table 2).…”
Section: Pcr Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…Recent Polish and Iranian studies suggested that there was a significant association between the number of abortions and abnormal vaginal discharge with C. trachomatis infection 18,19 . This study detected a relationship between several ectopic pregnancy and presence of C. trachomatis antigen whereas the p-value was (0.008) this was agreed with Abdolreza et al, who observed that presence of C. trachomatis antibodies with an ectopic pregnancy patients 20 .…”
Section: Fig 2: the Percentage Of Women Who Had A History Of Infectimentioning
confidence: 99%